Rights Protection Guarantee for the Partners of Indonesian Gojek Company according to Labour Laws no 13 of 2033 and Maqasid - Yahya, Abdullah Muhammad; Hasan, Moh Abdul Kholiq; AN, Andri Nirwana (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
Gojek is one of the largest electronic application companies that provides transportation and delivery services and has many driver-partners. In 2020, the number of business partners will reach two million partners. The research focuses on social conflicts, bad consumer attitudes, and punishments accompanied by dropping out of work against them. This study aims to analyze the guarantee of the protection of the rights of Gojek Indonesia's partners in the review of the Manpower Act No. 13 of 2003 and in terms of maqashid . This is a descriptive analysis research with content analysis method through the theory of the Manpower Act and sharia maqashid, then analysis through scientific data sourced from valid scientific books and journals. The findings of this study are in the form of an agreement between the driver-partners and the Gojek company, including a partnership agreement, there is not a work agreement. On this matter, the Manpower Law No. 13 of 2003 cannot be applied to driver-partners, therefore they are not entitled to claim the rights of the protection guarantees contained in the agreement. in the Manpower Act. As for Gojek's company policy, according to Ibn Ashur's maqashid sharia analysis, some disagree with the maqshad of freedom, the principle of equality and not by maqshad, eliminating every agreement that contains elements of slavery. In terms of the rights of the driver partners, it is by the maqshad of the maslahah principle and the fulfillment of rights to the experts, and the maqshad of providing work support facilities, as well as the maqshad of hastening the provision of wages. And in terms of partner facility services, everything is in line with the maqashid sharia principle.